Quality of life of a university community in remote work during the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: to assess the quality of life of professors, students and administrative technicians at a federal university working remotely during the pandemic. Method: observational, quantitative study, carried out with 203 professors, students and administrative technicians from a federal university in the interior of Minas Gerais. Data collection took place between August and September 2020, through an online form with questionnaires on sociodemographic/economic profile and health conditions and on QoL. Descriptive and inferential analysis was performed. Results: In general, having a partner, higher education and income, access to the internet by cell phone, not having a chronic illness and difficulty sleeping and positive self-assessment of health made the QoL better. A better QoL was observed among professors at the expense of students. Conclusion: it elucidates the need after the diagnosis raised with difficulties in QOL, psychological and emotional support measures will be necessary in the return of the academic community, with students, professors and technicians.